Temporal dynamics and interrelations of cytokines, neutrophil proteins, exudation, and bacterial colonization in epidermal wound healing - Lundgren, Sigrid; Petruk, Ganna; Wallblom, Karl; Cardoso, José F. P.; Strömdahl, Ann-Charlotte; Forsberg, Fredrik; Luo, Congyu; Nilson, Bo; Hartman, Erik; Fisher, Jane; Puthia, Manoj; Saleh, Karim; et al. (Frontiers in Medicine, 2025)
IntroductionInflammation is integral to wound healing; yet, its dynamics in normally healing epidermal wounds are not fully characterized. To this end, we analyzed longitudinal wound fluid samples collected from epidermal suction blister wounds in healthy volunteers.Materials and methodsA total of 48 control wounds were induced by suction blister method in 24 healthy volunteers—1 on each thigh. Immunoassay, MALDI-TOF mass spectrometry, and microbiological methods were applied to analyze cytokine dynamics, neutrophil activity, and bacterial colonization and levels in wound swabs and dressings during epidermal wound healing, focusing on viable cultivable wound bacteria.ResultsCytokine levels peaked on day 5, followed by a decline on day 8. Wound exudation, measured by protein content, increased from day 2, peaking on day 5. The neutrophil-derived proteins myeloperoxidase, elastase, and heparin-binding protein (HBP) peaked on day 5, correlating with interleukin (IL)-8, a key neutrophil chemoattractant. The identified bacteria consisted primarily of commensal bacteria, including various staphylococci. Levels of such bacteria rose from day 2, peaking on days 5–8, and aligned with increases in the cytokines tumor necrosis factor α, IL-1β, and IL-10 at the peak of inflammation on day 5.ConclusionsThis study uncovers the coordinated dynamics of cytokines, neutrophil activity, and major commensal bacteria in epidermal wound healing and identifies HBP—a marker for neutrophil activation and endothelial leakage—for the first time in normally healing epidermal wounds.